Delayed sexual maturity in males of Vespa velutina. (8th June 2017) - Poidatz, Juliette; Bressac, Christophe; Bonnard, Olivier; Thiéry, Denis
Abstract: Vespa velutina var nigrithorax (Lepelletier, 1835) is an invasive predator of bees accidentally introduced in France in 2004, and it is having a serious impact on apiculture and ecosystems. Studying the reproduction of an invasive species is key to assess its population dynamic. This study explores the sexual maturation of V. velutina males and the evolution of their fertility. The main studied parameters were physiologic (spermiogenesis, spermatogenesis) and anatomic (testes size and structure, head width). Two populations of males were described based on their emergence period: early males in early summer or classic males in autumn. Each testis has an average of 108 testicular follicles. Spermatogenesis is synchronous, with only 1 sperm production wave, and completed, on average, at 10.3 d after emergence with the degeneration of the testes. The sperm counts in seminal vesicles of mature males are 3 × 10 6 in October/November and 0.8 × 10 6 in June. In comparison, females store 0.1 × 10 6 sperm in their spermathecae. The early males emerged from colonies made by fertilized queens. The reproductive potential of these early males seemed limited, and their function in the colony is discussed. The sperm stock evolution in autumn males suggests the occurrence of a reproductive pattern of male competition for the access to females and a single copulation per male. The synchronicity of male and foundress emergences and sexual maturation is of primary importance for the mating success and the future colony development.